Development of a Web-Based Assignment Information System by Applying Leaderboard and Quest Gamification Elements at SMK Negeri 2 Surakarta - Rizal Taufiq Hidayat; Dwi Maryono; Cucuk Wawan Budiyanto (Journal of Informatics and Vocational Education, 2023)
This study aims to find out how to build a web-based assignment information system by applying Leaderboard and Quest gamification elements at SMK Negeri 2 Surakarta TKJ Expertise Program and determine the eligibility level developed according to ISO 25010 Standards. Information system development using the Laravel web application framework. Development is carried out using the agile development software development model consisting of 5 stages, namely planning to produce functional and non-functional requirements. The research applies the Object Oriented Analysis and Design (OOAD) method in the analysis and design process. Analysis produces use case diagrams, Design produces activity diagrams and class diagrams. Implementation produces program code from development results. The system produces products uploaded to the server, which can later be accessed online and in real time. This information system has three levels of users, namely admin, teachers and students. The suitability test results using the ISO 25010 Standard on the three sub-characteristics of functional suitability, namely functional completeness, have an average value of 1 (Good). Functional correctness has an average value of 1 (Good). Functional appropriateness has an average value of 1 (Good). Characteristics of performance efficiency obtained an average result of GTMatrix Grade 85% (grade B). The average largest contentful paint is 1.423s (OK, but considering improvement). Average total blocking time 97.82ms (Good - nothing to do here). Average cumulative layout shift 0.023 (Longer than recommended). Portability characteristics have excellent results in that the system can run on desktop or mobile devices. Usability characteristics of 85% (Very Decent). The results of the respondent gamification test average score of 4.44 indicate that respondents are categorized as strongly agreeing with the existence of a web-based assignment information system by applying leaderboard and quest gamification elements. From the results of these tests, it can be concluded that the web-based assignment information system, using Leaderboard and Quest gamification elements at SMK Negeri 2 Surakarta TKJ Expertise Program, meets ISO 25010 quality standards.